Transitory shocks, permanent effects: Impact of the economic crisis on the well-being of households in Latin America and the Caribbean - Fernández, Almudena; López Calva, Luis F. (Estudios Económicos de El Colegio de México, 2010)
This paper aims to measure the impact of the global crisis on social indicators child health, mortality, education and poverty in five Latin American countries. The results suggest that economic downturns have a negative impact on child mortality, child health, and both overall and child poverty. Child poverty increases at higher rates than overall poverty. Results on education indicators are ambiguous. The paper concludes that an integrated social protection policy that protects the income of poor households and that maintains or expands basic health services during economic downturns are of critical importance to prevent transitory shock from having permanent effects on the well-being of households.